Characteristics of Beef Rendang with the Addition of Red Ginger (Zingiber officinale var. Rubrum) During Storage at Room Temperature (Jurnal Ilmu dan Teknologi Hasil Ternak, 2022)
The addition of red ginger in the making of rendang was expected to increase antioxidants to prevent rancidity and increase the shelf life of rendang. This study aimed to analyze the physicochemical, organoleptic and antioxidant activity of beef rendang with the addition of red ginger at different levels based weight of meat (0%, 15%, and 30%). The tested rendang was stored in a tightly closed jar and left at room temperature. The results showed that the interaction of the addition of red ginger and storage period had a significant effect (p<0.05) on the pH value, water activity, moisture, protein content, TBARS value, and antioxidant activity, but has no significant effect on ash content, fat content, and tenderness. Ash and fat content as well as tenderness of beef rendang added red ginger were not different from beef rendang not added red ginger (control). Based on sensory test the addition of red ginger did not affect the preference of the panelists. The addition of red ginger to the manufacture of beef rendang has a positive effect on physicochemical characteristics and increases antioxidant activity. Generally, red ginger addition as much as 30% resulted the best result.